A remote sensing assessment of anthropogenic-induced wetland degradation of the Vietnam Mekong River Delta - Cao, Xuan Cuong (Curtin University, 2016)
Wetlands are one of the most important components shaping the natural landscape of the Vietnam Mekong River Delta (VMRD). The assessment of wetland change is particularly important for their management in this region. This study monitors the change of wetland in western VMRD from 1998 to 2016 using remotely sensed imagery and multiple data fusion techniques. Key results indicate that grassland has experienced a significant loss of between 71.9-78.5% since 1998 due to land-use diversification.